Teun A. Van Dijk Discourseanalysis of Gender Issues in the Samjin Company English Class Film - Ulul Fikri Hasibuan; Ahmad Tamrin Sikumbang (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
Gender discrimination is the difference in treatment between men and women in the fulfillment of their rights in social life. This research using qualitative descriptive method analyzes the text discourse structure contained in the Samjin Company English class film with the Slice of Life genre. It tells the story of three female employees who try to get promotions at their company in the midst of rampant gender discrimination at that time in 1995. Through the discourse analysis of Teun A Van Dijk, a model from several dimensions of analysis was found, including the text dimension, social cognition dimension and social context dimension. From the results of the study, it was found that discrimination is a very wrong thing in understanding gender equality. The director and screenwriter of this film, who likes to criticize gender issues in his work, agrees with these things.